Evaluation of catechin, lupeol, and betulinic acid as markers for the chromatographic quality Control of Albizia coriaria raw materials; an experimental study - Kaggwa, Bruhan; Munanura, Edson Ireeta; Kyeyune, Henry; Anywar, Godwin; Okella, Hedmon; Ajayi, Clement Olusoji; Wangalwa, Raphael; Mulangwa, John; Sesaazi, Crispin Duncan; Bagoloire, Lynn K.; Tolo, Casim Umba; Kamba, Pakoyo Fadhiru; et al. (Journal of Medicinal Plants Research, 2023)
Albizia coriaria stembark is among the most common raw materials used to manufacture herbal products in Uganda. While the plant material is sourced from the wild, there are neither monographs nor chemical analytical methods for its standardisation. In addition, good cultivation, harvesting, and manufacturing practices are not mandatory. This leads to inconsistent quality of raw materials and products. This work developed TLC and HPLC methods and evaluated the suitability of lupeol, catechin, and betulinic acid markers for standardization of stembark from A. coriaria. Samples were extracted by decoction, maceration and soxhlet reflux; in water, ethanol and ethyl acetate. Catechin, lupeol and betulinic acid markers were found in all batches of A. coriaria from different agroecological zones, at concentrations higher than 6mg/g. Ethyl acetate fractions gave the highest marker quantities, while decoction gave the lowest. The optimised TLC fingerprint conditions were solvent system: 4, 2, 1 and 1 parts of n-hexane, ethyl acetate, dichloromethane, and methanol, respectively; stationary phase; TLC glass plates, 10 cm × 20 cm, coated with fluorescent 60Å silica gel matrices and vanillin / sulfuric acid spray reagent. The resulting fingerprints comprised of twelve principal peaks. The optimized conditions of the HPLC fingerprint and quantitation method were: C18 column (250 × 4.6 mm x 5 µm), solvent system; acetonitrile (99.99%) and 1% trifluoroacetic acid (0.01%); flow rate, 1mL/min; column temperature, 25°C; and UV/visible detector 205 nm. The common HPLC fingerprints had correlation coefficient >0.99, while quantitative methods were accurate (>97% recovery) and reproducible (RSD < 0.38%). Lupeol and betulinic acid are suitable markers for the quality control of Albizia coriaria raw materials. decoctions are better controlled by catechin.
Keywords: Markers; Fingerprints; Albizia coriaria; Betulinic acid; Lupeol; Quality control; Standardisation